ECOLOGICAL STUDY OF LITERATURE IN GEGURITAN KENDENG KAYA AMBENG - Gunawan, Eko (Yayasan Education and Social Center, 2025)
This study aims to examine the Kendeng Kaya Ambeng geguritan text using literary ecology. This research uses qualitative descriptive research. The data were collected using reading and note-taking techniques. This research utilises literature study techniques to strengthen the primary data collected. After that, the collected data are processed through a series of stages, including 1) data selection, 2) data interpretation, and 3) concluding the research results. Through a literary ecology approach,